IMPROVEMENT OF ACCOUNTING ELEMENTS IN THE CONTEXT OF DIGITAL MODERNIZATION OF THE ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The rapid development of the digital economy, both worldwide and in our country, affects all areas of activity, including accounting processes.  Accounting in theoretical and practical terms, is also undergoing significant changes.  However, the methodology and tools of accounting do not always correspond to modern realities, due to which there are a number of problems associated with the implementation of digital solutions.  The enterprises automate the collection and registration of primary information using modern measuring instruments, which provides documentation of business transactions exclusively in electronic form.  Improvements in the theory and formation of the practice of accounting are theoretically combined with the expansion of the information potential of the existing economic space.  The article considers the expansion of the reflection of the scope of the organization in accounting;  improving the quality of information and efficiency of accounting, identification and increase in the number of new objects of accounting, development of innovative methods of evaluation of new objects of accounting, formation of approaches to integration of different types of accounting, use of modern information technologies of information collection and processing (blockchain technologies)  theoretical, methodological and applied aspects of accounting development.
Keywords: accounting, digitalization, documentation, inventory, valuation, electronic reporting, cost